INTERGENERATIONAL CARE SUPPORT TRANSFER: INSIGHTS FROM THE GENERATION AND GENDER SURVEY - Buciuceanu-Vrabie, Mariana; Grigoraș, Ecaterina (Economy and Sociology, 2023)
Understanding intergenerational transfers of childcare is crucial in the context of declining birth rates, changing family structures, and population aging. Informal assistance in childcare is highly significant for many families with young children as it helps them balance their professional and parenting responsibilities. Existing research indicates that support provided by parents to their adult children in childcare positively impacts decisions regarding childbirth and women's participation in the labor market. The aim of this study is to analyze patterns of support transfer between different generations and identify factors influencing intergenerational transfers in Moldova. It is based on data from the "Generations and Gender" (GGS) study conducted in 2020. Thanks to its representative sample, the study encompasses aspects such as intergenerational transfers related to childcare and grandchildren, attitudes toward childcare, and socio-demographic variables. Statistical analysis involves cross-tabulations and logistic regressions to identify factors determining participation/transmission of support in childcare. The research findings demonstrate that grandparents provide significant assistance to their adult children in childcare, particularly during the initial years of the child's life. This support is predominantly received by women with young children and women with higher education with children. Typically, childcare assistance is offered by grandparents approaching pre-retirement and retirement ages. Factors such as children's ages, family size, level of education, and urban residence significantly influence the receipt of childcare assistance. The results underscore the importance of traditional values and societal expectations, providing a nuanced understanding of intergenerational relationships amidst a changing demographic landscape. They could prove valuable for policymakers and developers of programs supporting families with children.